2012
DOI: 10.48084/etasr.139
|View full text |Cite
|
Sign up to set email alerts
|

A Decision-Analytic Feasibility Study of Upgrading Machinery at a Tools Workshop

Abstract: This paper presents the evaluation, from a Decision Analysis point of view, of the feasibility of upgrading machinery at an existing metal-forming workshop. The Integral Decision Analysis (IDA) methodology is applied to clarify the decision and develop a decision model. One of the key advantages of the IDA is its careful selection of the problem frame, allowing a correct problem definition. While following most of the original IDA methodology, an addition to this methodology is proposed in this work, that of u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Reviews of dynamic simulation applications for optimizing energy and chemical systems are shown in [3,4], while applications of discrete event simulation to the optimization of industrial systems can be found in [4][5][6]. Usage of simulation in specific situations are presented in [7] for sustainable plant design, in [8] for gasifier pressure modeling, and in [9] for analyzing a petrochemical process wastewater plant.…”
Section: A Literature Reviewmentioning
confidence: 99%
“…Reviews of dynamic simulation applications for optimizing energy and chemical systems are shown in [3,4], while applications of discrete event simulation to the optimization of industrial systems can be found in [4][5][6]. Usage of simulation in specific situations are presented in [7] for sustainable plant design, in [8] for gasifier pressure modeling, and in [9] for analyzing a petrochemical process wastewater plant.…”
Section: A Literature Reviewmentioning
confidence: 99%